ABOVE-GROUND CARBON POOLS OF CITRUS ACREAGE IN PAKISTAN - B. Akram; F. Abbas; M. Ibrahim; M. F. Nawaz; S. I. Zahra; M. R. Salik; H.M. Hammad (Journal of Animal and Plant Sciences, 2017)
Estimation of above-ground biomass (AGB) is important for forest resource inventory, natural resource management and environmental services such as estimation of carbon sequestration. Objective of this study was to estimate AGB of citrus trees using a non-destructive method and quantify carbon pools of citrus acreage in Pakistan. One hundred trees of different age were selected at three various locations in Faisalabad Division to achieve the study objective. Measurements of tree height, breast height diameter, wood density and green volume were made using standard methods. Regression equations were used to estimate AGB of citrus plants from above plant variables. Total carbon sequestered by citrus cultivation in Pakistan was estimated to be 1176 tons from the data of citrus acreage in Pakistan with an average density of 40 plants ha-1. Field implications of this research include estimation of environmental services of forestation and managing agro-ecosystems. Total amount of carbon sequestered by citrus orchards of various ages can be estimated by the relationships established in this study. These research results may be used as baseline information for future studies and planning and management of carbon budgets in Pakistan.
Keywords: Plant biomass; carbon sequestration; environmental services; plant variables; agro-forestry